An Analysis of Slang Language used in Daily Conversation by The Students of 4th Semester of Batanghari University - Ismiyati, Yanti (Universitas Batanghari Jambi, 2025)
This research deals with the slang language word that used in daily conversation among the students at 5th semester in University of Batanghari Jambi. The aims of the research as the following below: (1) to know about the form of which is used by the students of 4th semester of Batanghari University in their daily conversation; (2) to know about the reason that motivated the students of 4th semester in English department University of Batanghari to use slang language in their daily conversation. The methodology used in this research is a qualitative. The data took by recording and interview of subject of the research. The conclusion of the research is overall, students have a positive perspective towards the use of slang. They see it as a way to express themselves, connect with friends, and stay relevant to cultural trends.